Behaviors of Providers of Traditional Korean Medicine Therapy and Complementary and Alternative Medicine Therapy for the Treatment of Cancer Patients - Jun-Sang Yu; Chun-Bae Kim; Ki-Kyong Kim; Ji-Eun Lee; Min-Young Kim (Korean Pharmacopuncture Institute, 2015)
Objectives: In Korea, cancer is one of the most important causes of death. Cancer patients have sought alternative methods, like complementary and alternative medicine (CAM) together with Western medicine, to treat cancer. Also, there are many kinds of providers of CAM therapy, including providers of Korean oriental medicine therapy. The purpose of this study is to identify the behaviors of Korean oriental medicine therapy and CAM therapy providers who treat cancer patients and to provide background knowledge for establishing a new policy with the management and quality control of CAM. Methods: Structured and well organized questionnaires were made, and 350 persons were surveyed concerning the providers of CAM or Korean oriental medicine. The questionnaires were collected and analyzed. Results: The questionnaires (182) were collected. The questionnaires identified a total of 73 known providers, such as medicinal professionals or other providers of CAM suppliers, 35.6% of whom had had experience with treating cancer patients (52.6% vs. 29.6%). The treatment methods were a little different: alternative therapy and nutritional therapy being preferred by medicinal professionals and mind body modulation therapy and alternative therapy being preferred by other CAM providers. Four patients (7.4%) experienced side effects, and 6 patients (12.5%) experienced legal problems. As the method for managing the therapy, CAM providers, medicinal professionals, and other CAM providers had different viewpoints. For example, some CAM providers stated that both legislation and an official education on CAM or a national examination were needed as a first step to establish the provider's qualifications and that as a second step, a license test was needed for quality control. To the contrary, medicinal professionals stated that a license test was needed before legislation. Conclusion: Adequate management and quality control of CAM providers is thought to involve both education and legislation.